Bachelor Level Student's Perspective on Teaching Methodology: Traditional vs. Modern - Bhandari, Ashok; Bhandari, Pradip (Journal of Vishwa Adarsha College, 2024)
This study attempts to examine the present need for teaching methodology from the perspective of learners. It studies the ground-level opinion of students of Kathmandu Valley studying at the bachelor’s level regarding traditional and modern teaching methodology. It is based on information provided by students collected through questionnaires and interviews, based on 536 respondents aged 18-22. The findings might be contrary to our existing knowledge and expectations of modern teaching methodology as most students were not ready to accept and adapt to modern teaching methodologies such as PowerPoint slides, group discussions, quizzes, etc. Even though their belief in modern teaching methodology was somehow positive, the study revealed that students still were not used to the modern method of teaching. They were unprepared to be independent learners and still depend on their teachers. This study implies that if universities and institutions in Kathmandu favor adopting modern teaching methodology as believed to be the best alternative to traditional teaching methods, student orientation and practice about modern methods is required.